2017
DOI: 10.1200/jco.2017.35.15_suppl.e21022
|View full text |Cite
|
Sign up to set email alerts
|

Total tumor burden as predictive tool of response and survival of patients with metastatic melanoma treated with nivolumab.

Abstract: e21022 Background: Nivolumab (NIVO) has shown increased results either in objective response rate (ORR), progression free survival (PFS) and overall survival (OS), which have completely changed the treatment of patients with metastatic melanoma (MM). Tools to guide selection of patients are absent Methods: This is a retrospective, observational, single-center study. The TBT was calculated considering the sum of the largest diameter of all measurable lesions and the smallest diameter of lymph nodes affected Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The findings in this study are comparable to those of De Moares et al, who retrospectively analyzed the SOML of 54 patients with metastatic melanoma and demonstrated higher PFS for patients with a tumor burden < 200 mm 22 . Another recently published study examined the association between baseline tumor size and several clinical outcomes among patients with metastatic melanoma treated with pembrolizumab.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The findings in this study are comparable to those of De Moares et al, who retrospectively analyzed the SOML of 54 patients with metastatic melanoma and demonstrated higher PFS for patients with a tumor burden < 200 mm 22 . Another recently published study examined the association between baseline tumor size and several clinical outcomes among patients with metastatic melanoma treated with pembrolizumab.…”
Section: Discussionsupporting
confidence: 88%
“…This finding is in contrast to several other studies demonstrating the prognostic potential of functional imaging in NSCLC, 21 and may be attributed to a small sample size. 22 Another recently published study examined the association between baseline tumor size and several clinical outcomes among patients with metastatic melanoma treated with pembrolizumab. In their study, Joseph et al showed that a baseline tumor size > 102 mm (the median tumor size in the cohort) was associated with lower response rates and worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Shedding of ctDNA is a complicated process affected by many factors and tumor burden is one of the most important determinants 24 . On the other hand, tumor burden is also a well-known prognostic factor associated with patient survival across different cancer types 28 31 . Therefore, it is not unreasonable to hypothesize that ctDNA levels may simply reflect tumor burden that in turn is associated with survival.…”
Section: Discussionmentioning
confidence: 99%